Investigations on the spall and delamination behavior of UHMWPE composites. (15th December 2017) - Lässig, Torsten; Bagusat, Frank; Pfändler, Siegfried; Gulde, Max; Heunoske, Dominic; Osterholz, Jens; Stein, Werner; Nahme, Hartwig; May, Michael
Abstract: Composite materials in armor applications are commonly subjected to different deformation and failure mechanisms, which result in delamination of the solid laminate. Direct planar plate impact experiments were executed in order to study spall behavior of Dyneema ® HB26. For the first time, the spall behavior of UHMWPE composites was determined by evaluating the free surface velocity measured via Photonic Doppler Velocimetry (PDV). High-speed camera images from lateral view revealed that spall failure of UHMWPE composites, unlike e.g. metals or ceramics, is not restricted to a single crack plane. Instead, the spallation of the composite plates in through-thickness direction caused by the first release wave is accompanied by several delaminations at ply interfaces, which are caused by intersections of subsequent release waves.